The BMJ Appeal 2024-25: Starvation and malnutrition escalating the threat of Sudan’s civil war - Feinmann, Jane (BMJ (Online), 2024)
Getting aid to the millions facing “mass starvation” in Sudan’s brutal and escalating civil war is a top priority for the International Rescue Committee (IRC), the subject of this year’s BMJ appeal. Jane Feinmann reports